2008
DOI: 10.1086/587892
|View full text |Cite
|
Sign up to set email alerts
|

Medical‐Grade Honey Kills Antibiotic‐Resistant Bacteria In Vitro and Eradicates Skin Colonization

Abstract: Revamil is a promising topical antimicrobial agent for prevention or treatment of infections, including those caused by multidrug-resistant bacteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
105
1
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(122 citation statements)
references
References 31 publications
4
105
1
3
Order By: Relevance
“…Many in vitro studies have shown antimicrobial activity of different honeys against a wide range of skin-colonizing and foodborne bacterial species, including antibiotic-resistant bacteria (Mundo et al 2004;Lusby et al 2005;Lin et al 2009;Kwakman et al 2008Kwakman et al , 2010. It has been shown that also in vivo honey has beneficial actions against wound infections (Robson et al 2009), and licensed honey products are widely used in wound care (Cooper et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Many in vitro studies have shown antimicrobial activity of different honeys against a wide range of skin-colonizing and foodborne bacterial species, including antibiotic-resistant bacteria (Mundo et al 2004;Lusby et al 2005;Lin et al 2009;Kwakman et al 2008Kwakman et al , 2010. It has been shown that also in vivo honey has beneficial actions against wound infections (Robson et al 2009), and licensed honey products are widely used in wound care (Cooper et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is crucial to find effective strategies to increase the DO concentration at the bottom of the biofilm and create a more acidic environment. Hyperosmotic concentrations of agents, such as medical-grade honey (48,49) and cadexomer iodine (50,51), have been considered for wound treatment. Recently, it was shown that hyperosmotic concentrations of maltodextrin increased the efficiency of vancomycin against S. aureus biofilms by reducing biofilm coverage, thickness, and diffusion distance, as well as by improving the DO concentration within the biofilm (37).…”
mentioning
confidence: 99%
“…This is in agreement to the work done by Ball (2007), showing that honey is acidic. Moreover, high osmotic effect (about 80% wt/vol of concentrated sugars) (Ramalivhana et al, 2014) and microorganism sensitivity to hydrogen peroxide (produced by glucose oxidase originating from the bees) found in honey (Ramalivhana et al, 2014;Paulus et al, 2008) constitute inhibitory factors to bacterial growth (Amal, 2014;Manisha and Shyamapada, 2011).…”
Section: Ph Of Samplesmentioning
confidence: 99%